Morphological and phytochemical studies of Suaeda maritima (L.) Dumort growing along the coastal belt of Purba Medinipur District, West Bengal, India in search of the prospective variation - Pati, Maniklal; Nandi, Asis Kumar (Current Botany, 2022)
Suaeda maritima (L.) Dumort of the family Chenopodiaceae is an annual succulent mangrove herb. This annual salt marsh is quite regularly used by the local people for food and pharmaceutical. This species has been cursorily noted to have variation in some morphological characters. Earlier reports indicated the presence of triterpenoid e.g. alpha amyrin in some species of Suaeda. However, no report on the variation in the quantity of it in this species was presented. The present study has furnished an account of subtle variation in morphology of this herb growing on different sites in the area under study. It also shows a difference in the amount of alpha amyrin in the plant individuals of different places, revealed through the HPTLC study. Morphological variations have been noted mostly in respect of the characteristics of the stem and leaf of the species.